Efektivitas Edukasi Perpajakan Melalui Program Kelas Pajak Seputar E-Faktur Dan PKP “Kang Kasep” Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak - Difa Nur Asyiami; Mira Permata Sari (Jurnal Ilmu Administrasi Publik, 2026)
Tax compliance remains a challenge at KPP Pratama Bekasi Utara, where the number of Taxable Entrepreneurs (PKP) has grown from 3,489 (2021) to 4,654 (September 2025) amid the transition from the e-Faktur system to the Coretax Administration System. This situation prompted KPP Pratama Bekasi Utara to establish the Tax Class Program on e-Faktur and PKP known as "Kang Kasep" as a formal educational initiative for newly registered PKP. This study aims to measure the effectiveness of the program in improving the understanding and compliance of new PKP. A descriptive qualitative approach was employed, using the Effectiveness Theory proposed by Edy Sutrisna in Human Resources (2010:123). The findings indicate that the program is sufficiently effective in providing technical and administrative understanding. However, its effectiveness is constrained by the heterogeneity of participants' backgrounds, rapid regulatory changes, and a lack of hands-on practice sessions. Strengthening material delivery, adding technical practice sessions, and providing structured learning modules are recommended to optimize the program's effectiveness going forward. Keywords effectiveness; tax class program; Kang Kasep; tax compliance; Taxable Entrepreneurs (PKP)